Anti-diabetic activity of Leptospermum flavescens leaves using in vitro and in vivo models / Ahmad Fadhlurrahman Ahmad Hidayat - Ahmad Fadhlurrahman , Ahmad Hidayat (2018)
Leptospermum flavescens Sm. (Myrtaceae) locally known as gelam bukit has been used traditionally to treat various ailments such as constipation, hypertension, diabetes, and cancer. To date, there is still limited scientific evidence on L. flavescens inducing anti-diabetic activity. Thus, the aim of the present study was to investigate the anti-diabetic effects of L. flavescens using in vitro and in vivo models. L. flavescens extraction yielded four extracts: hexane, ethyl acetate, methanol, and water extracts. The methanol extract of L. flavescens (MELF) revealed the highest biological activity such as exerting the greatest antioxidant activity, promoting the highest α-amylase and α-glucosidase inhibition, protecting INS-1 β cells against streptozotocin (STZ) induced apoptosis (with cell recovery up to 91.12 %) and increasing INS-1 β cells insulin secretion. Furthermore, MELF was found to inhibit apoptosis in STZ-induced INS-1 β cells according to Annexin V/PI, Hoechst 33342/PI, mitochondria membrane potential (MMP) and western blot assay. Besides, MELF inhibited autophagy and induced AKT and GSK-3β protein expression based on western blot assay. MELF was shown to regulate the redox potential by increasing intracellular catalase activity and inhibiting intracellular reactive oxygen species (ROS) production. The redox regulation was further corroborated by HO-1 and Nrf-2 protein expression towards STZ-induced INS-1 β cells. MELF treatment of 2 g/kg showed no signs of toxicity observed in Sprague Dawley (SD) rats for 14 days as confirmed by histopathological and biochemical analysis. MELF was found to reduce fasting blood glucose (FBG) as evidenced by oral glucose tolerance test (OGTT). Additionally, MELF also induced hypoglycemic effects in STZ-NA-induced SD rats. MELF also promoted insulin production in STZ-NA-induced SD rats based on immunohistochemistry assay. Notably, MELF stimulated its pancreas-protective effects via inhibition of cleaved caspase 3 and LC3A/B proteins based on immunohistochemistry assay. Furthermore, MELF was shown to increase HDL and reduce LDL levels in STZ-NA induced SD rats. Therefore, based on the cumulative results, MELF might hold plausible anti-diabetic activity.